Nutrition education and anemia prevention in efforts to prevent stunting from upstream at SMP Taruna Mandiri - Aldriyanshah Zaefri Anshari; Hasna Athaya Rifa (Universitas Pendidikan Indonesia, 2024)
Stunting and anemia are health problems that need to be considered during adolescence. Anemia is a condition of blood deficiency caused by a lack of iron nutrition which can cause various problems such as weakness, fatigue, and so on. This can certainly affect adolescents who are of productive age, such as school students. On the other hand, students do not understand the dangers of anemia and stunting themselves. This community service aims to provide understanding or education to students of SMP Taruna Mandiri regarding the dangers of stunting, prevention of anemia, and emphasis on the consumption of Iron Supplement Tablets (IST). Community service is carried out by designing a concept for socialization, observation, and surveys to 102 students. The survey showed that the majority of students of SMP Taruna Mandiri do not routinely consume Iron Supplement Tablets (IST) even though the school has routinely provided IST every month. So it is known that student awareness regarding the importance of consuming IST and maintaining health to avoid anemia is still lacking. Therefore, socialization of IST consumption and prevention of anemia is needed and carried out routinely. Abstrak Stunting dan anemia menjadi masalah kesehatan yang perlu diperhatikan pada masa remaja. Anemia merupakan kondisi kekurangan darah yang diakibatkan kurangnya nutrisi zat besi yang dapat mengakibatkan berbagai masalah seperti lemah, cepat lelah, dan lain sebagainya. Hal ini tentunya dapat memengaruhi remaja yang ada pada umur produktif, seperti peserta didik sekolah. Di sisi lain, peserta didik kurang memahami bahaya dari anemia dan stunting itu sendiri. Pengabdian ini bertujuan untuk memberikan pemahaman atau edukasi kepada peserta didik SMP Taruna Mandiri terkait bahaya stunting, pencegahan anemia, dan penekanan konsumsi Tablet Tambah Darah (TTD). Pengabdian dilakukan dengan perancangan konsep sosialisasi, observasi, dan survei kepada 102 peserta didik. Survei menunjukkan bahwa mayoritas peserta didik SMP Taruna Mandiri tidak rutin mengonsumsi TTD meskipun sekolah telah secara rutin memberikan TTD setiap bulannya. Sehingga diketahui bahwa kesadaran peserta didik terkait pentingnya konsumsi TTD dan menjaga kesehatan agar terhindar dari anemia masihlah kurang. Maka dari itu, sosialisasi konsumsi TTD dan pencegahan anemia dibutuhkan dan dilangsungkan secara rutin. Kata Kunci: anemia; sosialisasi; stunting